Provenance of Albian sandstones (Itapecuru Group), eastern border of São Luís-Grajaú Basin, Maranhão, using heavy mineral analysis and mineral chemistry - Mendes, Anderson Conceição; Truckenbrodt, Werner (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2009)
Albian deposits from the São Luis-Grajaú Basin, formerly recognized only in the subsurface, have been recently found along the Itapecuru river, eastern part of this basin. These deposits consist of red, gray to greenish mudstones, cross-bedded and massive sandstone and subordinately limestones, interpreted as deposits of a to ENE/E and ESE prograding delta connected to a restricted platform. In order to understand the provenance of Albian sandstones, 18 samples were collected for heavy mineral analysis (fraction 0,062-0,125 mm) using a conventional petrographic microscope and scanning electron microscope. The sandstones have been classified as moderately to well sorted, dolomite-cemented quartz-arenites whose heavy-mineral suite consists of zircon (4-70%), garnet (12-74%), tourmaline (3-20%), staurolite (1-9%), rutile (1-8%) and baryte (0-55%), while kyanite, anatase (authigenic), calcic-amphibole, andalusite, sillimanite, spinel and ilmenite occur more rarely. The majority of the grains is angular irregular, but well rounded grains, particularly tourmaline and zircon, are also present. Surface textures include conchoidal fractures, percussion marks in V and diminute pits, the latter in rounded tourmaline and zircon grains, while corrosion features are mainly present in baryte (rhombic cavities), kyanite, staurolite (surface mammillae) and garnet (well-formed etch-facets). Zircon grains, with oscillatory zoning textures, U/Th ratio ≥ 0,5 and mean Zr/Hf ratio of 29, are mainly derived from granites and probably migmatites. Plots on Zr/Hf-Y and Hf-Y-Nb diagrams show that this mineral can be related to at least two different sources. The tourmaline types, determined as dravite and schorl, indicate provenance mainly from aluminous and/or Al-poor metapelites and metapsammites with smaller contribution from granitic and meta-ultramafic rocks. Garnet is rich in almandine and has relatively low spessartine, grossular and pyrope contents whose potential source rocks are low- to medium-grade metamorphic rocks and granites. Based on their heavy-mineral suite and the progradation of the delta system to ENE/E and ESE, the most likely source areas of the studied Albian sandstones are the São Luís Craton, the Neoproterozoic Araguaia and Gurupi belts as well as the Paleozoic Parnaíba Basin, the latter supplying sediments of rounded grains.
Keywords: Provenance; Heavy minerals; Albian sandstones; São Luís-Grajaú Basin